Connecting the Continent: the drivers of participation in Africa's digital economy - de Villiers, Jacques (Graduate School of Business (GSB), 2023)
While technology has reshaped the economic landscape over the past decade, disruptive technologies also contribute to economic and social inequalities between ‘connected' and ‘unconnected' countries and individuals. For technology to fulfil its economic and social potential (creating jobs, access to health, etc.), the foundation for a digital economy must be present: digital infrastructure, basic and higher education, digital literacy and skills, social platforms, financial services, and entrepreneurial innovation. To unlock the benefits of internet usage among households in sub-Saharan Africa, and the subsequent injection of money and talent into the continent's digital economy, it is crucial to identify the key constraints faced by individuals in adopting internet services. The current study draws on the theoretical and empirical literature to construct and test hypotheses for internet adoption in South Africa, Nigeria, and Kenya. Specifically, this study examines three unique sets of determining factors of mobile internet adoption: a) physical infrastructure (electricity supply); socioeconomic factors (income level, urban or rural location, age, and education level, and c) perspective factors (number of close friends on social media platforms, and face-to-face time with interest groups) shaped by network effects. This study has found that the most significant determinant of internet adoption across all three countries is education level. Increasing rates of tertiary education could help catalyse internet adoption and meaningful participation in the digital economy, over the coming years. In terms of the physical access dimension of internet adoption, even though the expectation was that electricity access would not be positively correlated with internet adoption in South Africa, those with electricity access were found to be 2.4-times more likely to be connected than those without electricity access. In Nigeria, those with access to electricity were almost 2-times more likely to be internet users, while electricity access was not statistically significant for internet adoption in Kenya. In terms of the perspective dimension of internet adoption, having close friends on social media was found to be a strong determinant of being connected to the internet across all three countries